APLIKASI PENILAIAN PERSENTASI MAHASISWA BERBASIS WEB - Azis, Muhammad Rais (Department of Electrical Engineering, University of Patria Artha, 2021)
This type of research is experimental, namely by designing, making and testing system models. The percentage of student activities in certain subjects is often carried out by lecturers to assess students' ability in understanding course material. This presentation activity is carried out by students per group. The number of groups depends on the course material and also the number of students in one class. This student percentage assessment application aims to be used by students to provide an assessment of the percentage results of the group conducting the percentage. Furthermore, students can see directly the value obtained from the percentage results. The percentage value is displayed in tables and graphs. The use of the CodeIgniter framework is very helpful for researchers in making percentage assessment applications